高齢の配偶者が介護老人保健施設に通いながら夫婦としての生活を続けるプロセス - 原沢 優子; 山田 紀代美 (日本看護研究学会雑誌, 2011)
The purpose of this study was to clarify the process by which spousal caregivers can continue the conjugal relationship through their partner's move to an institutional setting. The participants were 9 former spousal caregivers, aged over 65 years, whose partners now resided in a geriatric health service facility. Data were collected by semi-structured interview, and were analyzed qualitatively and inductively. The findings revealed that the process is constructed of two steps. The first step is the decision-making process in which the spousal caregivers ask themselves what their motivation to care for their partner is and ultimately prepare to continue forward with their life by utilizing a care facility. The second step is a circular type process in which their preparation to continue forward circulates between two states: "sluggish preparation" owing to a factor which makes them 'disinclined to live', and "re-preparation" owing to a factor which 'motivates them to continue their conjugal life', A third factor affects both states. The spousal caregivers led an erratic life, but the option for their spouse to move into an institutional care setting enabled them to continue their conjugal life. 本研究の目的は，配偶者介護者が介護老人保健施設に通いながら夫婦としての生活を続けるプロセスを明らかにすることであった。配偶者が施設介護を受けている65歳以上の介護者９名を対象に，半構成的面接法を用いて質的帰納的に分析した。その結果，夫婦としての生活を続けるプロセスは二段階で構成されていることが明らかになった。第一段階は，自分自身の『動機を探索する』ことで，施設を利用してでも夫婦としての生活を続ける「覚悟を決める」意思決定のプロセス。第二段階は，介護生活の中で『生活する意欲を減退する要因』により「覚悟が揺らぐ」，『夫婦生活を持続する原動力』によってそれを乗り越え再度，「覚悟を決める」循環を繰り返す円環型プロセスであった。また，その　『両方に影響する要因』もあった。配偶者介護者は，このような生活を過ごしながらも，施設に入所している要介護配偶者と夫婦としての生活を続けていた。